RÉSOLUTION DE PROBLÈMES PAR VOIE DE SIMILITUDE AVEC CELUI DE LA SANTÉ: L'EFFICIENCE DES MOYENS - Pagé, Michel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
The objective analysis of a situation or an observation obtained in a specific domain can be beneficial to the resolution of a problem or contribute to a better understanding in another domain. The understanding from the prevention paradox of preventive epidemiology is particularly relevant to the field of education and teaching. Transposition of this paradox as a working hypothesis suggests that: (1) a measure introduced for the benefit of ail the student population offers little to each participating individual; (2) the increase in financial resources does not necessarily cause an increase in quality of schooling; and (3) measures introduced on a selective basis could be more beneficial to particular individuals. Furthermore, along with this analogical argumentation, a number of considerations indicate the fallacy of the argument according to which additional financial resources are necessary to the improvement of quality of teaching and schooling. Selected findings in this article, along with many field-tested experiences, suggest that fruitful similitudes between education and health might contribute to resolution of similar problems. RÉSUMÉ L'analyse objective d'une situation ou l'observation faite dans un domaine peut permettre des approches bénéfiques ou une meilleure connaissance dans un autre domaine. Les enseignements d'un paradoxe de l'épidémiologie de prévention nous ont paru particulièrement pertinents dans le domaine de l'éducation. Ce paradoxe, traduit comme hypothèse à l'essai, suggère que: 1. des mesures introduites pour l'ensemble des étudiants ne sont pas nécessairement bénéfiques pour chacun; 2. l'accroissement des moyens financiers ne garantit pas l'accroissement équivalent de la qualité de la formation; 3. des mesures particulières introduites sur une base sélective seraient plus aptes à produire des effets individuels bénéfiques. En outre un ensemble de considérations infirme, par analogie, le postulat selon lequel l'injection de ressources financières supplémentaires dans le secteur de l'éducation et de l'enseignement contribuerait à en accroître la qualité. A partir de constatations choisies, cet article ouvre la voie à la recherche de similitudes fructueuses entre la santé et l'éducation de façon à trouver des éléments de solutions à des problèmes analogues.